DAMPAK MIGRASI TERHADAP EFEKTIFITAS KOMUNIKASI LINTAS BUDAYA - W E Tinambunan (Jurnal Ilmu Komunikasi, 2012)
Impact of Migration on The Effectiveness Cross-cultural Communication. The study aimsto describe and understand a society as it is in the context of a whole or a whole round. Through the studywill describe in detail the social phenomena associated with the migration system. This study uses qualitativemethods which leads to the descriptive approach, which provides a situation and analyze the data based onthe data in the field. Subjects were local residents and migrants, community leaders and youth leaders at thedistrict level in number 250. The results showed that the factors driving the economy into a familyinformant to migrate to Bengkalis and there has been expansion of the family livelihood is not just as afarmer, but also followed by trade, entrepreneurs, workers, employees, civil servants and so on.